A politico-legal framework for integration in Africa : exploring the attainability of a supranational African Union - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2010)
The emergence of the African Union (AU) is seen as an effort to reposition Africa for the challenges of contemporary global realpolitik and, in particular, it provides a road map towards the attainment of a political union. The institutional architecture of the AU, modelled after the European Union (EU), indicates an intention on the part of the architects of the AU to endow the organisation with supranational attributes. However, none of its institutions has as yet started to exercise supranational powers. It is against this background that this thesis explores the feasibility of transforming the AU from a mere intergovernmental organisation into a supranational entity. In the course of the investigation, it was found that a major obstacle to realising this is the absence of shared democratic norms and standards, a consequence of the unconditional membership ideology of the AU. This thesis argues that the starting point of closer integration in Africa should be the cultivation and adoption of shared norms and values. To address this, the study proposes that the AU design an institutional mechanism for regulating its membership. Using the African Peer Review Mechanism (APRM) as a case study, this study shows that it is possible to establish a regulatory regime based on strict adherence to shared fundamental norms and values. A major recommendation is the transformation of the APRM into a legally binding instrument for setting continental democratic standards, assessing whether member states fulfil these standards and ultimately determining which member states are qualified, based on objective standards, to be part of a democratic AU.
https://repository.up.ac.za/handle/2263/28573
Keywords: African Union; African peer review mechanism; Regional economic communities (RECs); Regional integration

The New African Law: Beyond the Difference Between Common Law and Civil Law - Mancuso, Salvatore (Annual Survey of International & Comparative Law, 2010)

The Role of South Africa in SADC Regional Integration: the Making or Braking of the Organization - Amos, Saurombe (Journal of International Commercial Law and Technology, 2010)
Read on Neliti